Hygrothermoelastic analysis of orthotropic cylindrical shells - Syed Mohamed Ali, Jaffar; Alsubari, Saleh; Aminanda, Yulfian (Brazilian Society of Mechanical Sciences and Engineering, ABCM, 2016)
In this work, the combined effect of moisture and temperature on the bending behavior of simply supported orthotropic cylindrical shells has been investigated. Initially three dimensional equilibrium equa-tions of thermoelasticity, simplified to the case of generalized plane strain deformations in the axial direction are solved analytically for an orthotropic cylindrical shell strip under thermal loading. Based on the realistic variation of displacements from the elasticity approach, a new higher order shear deformation theory was proposed for the analysis of an orthotropic cylindrical shell strip under hygrothermal and mechanical loading. The zigzag form of the displacement is incor-porated via the Murakami zigzag function. Results are presented for mechanical and thermal loading for various layups and they are vali-dated against the derived elasticity solution. The significance of re-taining various higher-order terms in the present model, in evaluating the stresses and deflection for composite laminates is brought out clearly through parametric study. Useful results for combined hygrothermal loading are presented in tabular and graphical form. It is expected that the numerical results presented herein will serve as bench mark in future.